Negotiating gatekeepers and positionality in building trust for accessing the urban poor in the Global South - Lata, Lutfun Nahar (Qualitative research journal, 2021)
PurposeThis paper explores the importance of building trust and rapport with participants using gatekeepers and insider-outsider dynamics in accessing vulnerable research participants in the Global South.Design/methodology/approachThis paper draws data from a qualitative case study conducted in Sattola slum in Dhaka.FindingsFindings suggest that access to participants can be gained through building rapport and trust with participants. A trusting relationship further helps the researcher to explore the processes of social exclusion experienced by the participants.Originality/valueFew studies is published on female researchers building trust with vulnerable research participants negotiating gatekeepers and their subjectivity in the field. The paper contributes original insights into this from fieldwork carried out by a middle-class female researcher in Dhaka. It raises important issues in securing the trust of participants when they are part of disadvantaged, exploited or generally vulnerable populations.